2019
DOI: 10.1016/j.ijpsycho.2019.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Neural responses to criticism and praise vary with schizotypy and perceived emotional support

Abstract: Schizotypy is a latent organisation of a cluster of personality styles, such as magical thinking, disorganisation and anhedonia, which are in the normal range of the psychosis continuum. Schizotypy relates to an increased likelihood of perceiving expressed emotion (EE). EE is characterised by criticism, rejection, and emotional over-involvement and less warmth from a close relative. Neuroimaging studies have found normal frontal lobe activation to EE-criticism in people with high schizotypy. Alternatively, ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…Our results are consistent with those of previous studies. 16,19,21 However, in contrast to Ref. 18 , we found a minor difference in occipital connectivity patterns and we observed significant differences in interhemispheric connectivities between HS and LS groups.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…Our results are consistent with those of previous studies. 16,19,21 However, in contrast to Ref. 18 , we found a minor difference in occipital connectivity patterns and we observed significant differences in interhemispheric connectivities between HS and LS groups.…”
Section: Discussioncontrasting
confidence: 94%
“…14 Recent research has examined the EEG signals of individuals with high schizotypy (HS) in resting state [15][16][17][18][19] and during emotion and attention tasks. [20][21][22][23][24] Fuggetta et al 15 focused on power spectra of different EEG frequency bands and showed that HS participants elicited increased regional alpha oscillations. This abnormality suggested high-level attention in the HS group.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing work testing links between these traits and social reward processing has evidenced reduced responsivity to praise in schizotypy 21 , heightened feelings of social anhedonia related to reduced wanting of social interaction across the schizotypy continuum 22 , and increased subjective experience of Admiration and Negative Social Potency in dimensional psychopathy 9 . However, no work to-date has investigated similarities in social reward processing across these dimensions.…”
Section: Introductionmentioning
confidence: 99%